Group medical visits in the follow-up of women with a BRCA mutation: design of a randomized controlled trial - Hoogerbrugge Nicoline; Prins Judith B; Visser Annemiek; van Laarhoven Hanneke WM (BMC, 2011)
Abstract Background BRCA mutation carriers have a 40-80% life-time risk of developing breast cancer. They may opt for yearly breast cancer surveillance or for prophylactic mastectomy. Both options show increased survival rates. It is a complex choice to be made between these two options. As a result most women experience high levels of distress and high needs for information. To fulfill the needs for psychosocial support and information we have introduced group medical consultations (GMCs). A GMC provides individual medical visits conducted within a group. This 90 minute group-visit with 8-12 patients gives patients the opportunity to spend more time with their clinician and a behavioral health professional and learn from other patients experiencing similar topics. However, it should be noted that group sessions may increase fear in some patients or influence their decision making. Methods/design In this randomized controlled trial, 160 BRCA mutation carriers diagnosed maximally 2 years ago are recruited from the Radboud University Nijmegen Medical Centre. Participants are randomized in a 1:1 ratio to either the GMC intervention group (onetime participation in a GMC instead of a standard individual visit) or to a usual care control group. Primary outcome measures are empowerment and psychological distress (SCL 90). Secondary outcome measures are fear of cancer, information needs before the consultation and the received information, self-examination of the breasts, patient satisfaction, quality of life and cost-effectiveness. Data are collected via self-reported questionnaires 1 week before the visit, and at 1 week and at 3 months follow-up. A pilot study was conducted to test all procedures and questionnaires. Discussion The possibility for interaction with other BRCA mutation carriers within a medical visit is unique. This study will assess the effectiveness of GMCs for BRCA mutation carriers to improve empowerment and decrease distress compared to individual visits. If GMCs prove to be effective and efficient, implementation of GMCs in regular care for BRCA mutation carriers will be recommended. Trial registration The study is registered at ClinicalTrials.gov (NCT01329068)